PENGARUH MOTIVASI, DISIPLIN KERJA, DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT TELKOM AKSES SOLO - Monalisa Ayu Riskawati, Djumali & Istiqomah (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
This research in order to know how the of motivation, discipline and leadership against the work performance of employees of PT Telkom is a good Solo partially Access and simultaneously. Research methodology using quantitative research, with a population of 300 employees and 100 respondents totaled sample using questionnaire motivation, discipline and leadership against the work performance of employees of PT Telkom Akses Solo either partially and simultaneously. Technique of data analysis results showed that both are simultaneously addressed the value of F 17,627 test or a t test value of partial variables of motivation (4,643) proves there is significant motivation and a positive influence on performance of employees, variable working discipline (4,885) gives a positive and significant influence on performance of employees, and leadership variables (2,675) positive and significant influence on performance of employees. While the results of multiple linear regression shows the result of Y = 47,278 + 0,372 x1 + 0,286 x2 + x 0,572 x3.Keywords: Motivation, work discipline, leadership, employee performance.